2018
DOI: 10.1177/1528083718801365
|View full text |Cite
|
Sign up to set email alerts
|

The influence of component stiffness on the structure of multi-thread fancy bouclé yarn

Abstract: This study examines the relationships between the structure of fancy bouclé yarns and the bending stiffness of the input threads that are used to make those fancy yarns. Four fancy bouclé yarns and an extra two confirmation bouclé yarns were made to test the impact of the bending stiffness of the effect input threads. Six fancy yarns were made to test the impact of bending stiffness of the core thread on the fancy yarn structure. The structure of the fancy yarn was defined by using the Number of Fancy Profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A few other studies were concerned with the effect of the component yarns’ interactions on the whole structure. A study conducted to understand the interaction of bending stiffness of both the foundation and undulating components on the final yarn structure 4 confirmed the results of the previous study 3 and showed that a stiffer foundation component can produce larger undulations. In another study that tried to map the interaction of the overfeed ratio and the number of wraps, 5 it was shown that the ratio between the number of wraps and the overfeed ratio should be set to a specific value in order to control the formation of the resultant undulations.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…A few other studies were concerned with the effect of the component yarns’ interactions on the whole structure. A study conducted to understand the interaction of bending stiffness of both the foundation and undulating components on the final yarn structure 4 confirmed the results of the previous study 3 and showed that a stiffer foundation component can produce larger undulations. In another study that tried to map the interaction of the overfeed ratio and the number of wraps, 5 it was shown that the ratio between the number of wraps and the overfeed ratio should be set to a specific value in order to control the formation of the resultant undulations.…”
Section: Introductionsupporting
confidence: 76%
“…A few of other studies were carried out to understand the effect of false twist on the yarn structure and its tensile properties, 1 the effect of tension on the core or foundation component on the final structure 2 and the effect of the bending stiffness of the undulating or effect component. 3 The use of low tension on the foundation component may result in good quality bouclé undulations, which are being used in the traditional industry, whilst a low bending stiffness undulating component yarn helps to create a high number of regular small undulations while a high bending stiffness leads to a low number of irregular and larger undulations, producing undesirable appearance. It was also found that false twist should always be used to regulate the formation, appearance and number of undulations of the final structure.…”
Section: Introductionmentioning
confidence: 99%